TREATMENT OF PATIENTS WITH ARTERIAL HYPERTENSION AND METABOLIC SYNDROME. THE ROLE OF THE COMBINATION DRUGS - A. M. Shilov; M. S. Dulaeva; A. O. Osia; A. S. Lishuta (Столичная издательская компания, 2015)
Data about the current approach to the choice of dual antihypertensive combinations in various clinical situations for treatment of hypertension are presented. Advantages and indications for the combination of an ACE inhibitor with a dihydropyridine calcium channel blocker are reviewed. Data from prospective studies on the efficacy and safety of combination of third generation calcium channel blocker lercanidipine with ACE inhibitor enalapril are presented.